Corrective and Development Work of Teachers with Young Children With Disorders of Speech in the Process of Forming their Communicative Skills - Matveieva, Nataliia (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article describes the peculiarities of the teacher's activity in the process of correction of speech disorders of younger students and their overall development. Various approaches of scientists to the content of communicative activity of a person are described, its components are defined, the stages and components of the process of formation of communicative skills of younger students with speech disorders are outlined. Emphasis is placed on the need to differentiate the concepts of “communicative competence”. The author states that the development of communication skills of younger students with speech impairment is the main task not only of speech therapist, school psychologist, but also of the team of specialists of the educational institution. It is substantiated that the development of communication, speaking and communication skills is one of the prerequisites for comprehensive personality development.